2014
DOI: 10.1016/j.scitotenv.2014.04.082
|View full text |Cite
|
Sign up to set email alerts
|

An uncertainty and sensitivity analysis applied to the prioritisation of pharmaceuticals as surface water contaminants from wastewater treatment plant direct emissions

Abstract: A B S T R A C TIn this study, the concentration probability distributions of 82 pharmaceutical compounds detected in the efflu-ents of 179 European wastewater treatment plants were computed and inserted into a multimedia fate model. The comparative ecotoxicological impact of the direct emission of these compounds from wastewater treatment plants on freshwater ecosystems, based on a potentially affected fraction (PAF) of species approach, was assessed to rank compounds based on priority. As many pharmaceuticals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 54 publications
(63 reference statements)
0
11
0
Order By: Relevance
“…Most of the collected works on SSDs targeted a small dataset size or a restricted group of species. 27–32 A few notable attempts made to assess the SSD profile of a chemical using QSAR predictions using a limited number of compounds and species were by Tetko et al , 2013 and others, 33–35 or using additional parameters to already defined SSD models as observed with works of Bejarano et al , 2017 36 and Bejarano 2019, 37 or without incorporating any experimental ecotoxicity data (based on predictions). 38 Again, some of the SSD works incorporated non-linear machine learning tools such as artificial neural networks which offer limited use from the regulatory perspective.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the collected works on SSDs targeted a small dataset size or a restricted group of species. 27–32 A few notable attempts made to assess the SSD profile of a chemical using QSAR predictions using a limited number of compounds and species were by Tetko et al , 2013 and others, 33–35 or using additional parameters to already defined SSD models as observed with works of Bejarano et al , 2017 36 and Bejarano 2019, 37 or without incorporating any experimental ecotoxicity data (based on predictions). 38 Again, some of the SSD works incorporated non-linear machine learning tools such as artificial neural networks which offer limited use from the regulatory perspective.…”
Section: Resultsmentioning
confidence: 99%
“…The use of sewage sludge or recycled wastewater for agricultural purposes was also the subject of some of the analyzed case studies (e.g., Muñoz et al ; Hospido et al ). Additionally, some of the studies used LCIA models “solely” to rank and prioritize wastewater‐borne contaminants, including pharmaceuticals, in terms of their human and ecotoxicological impacts (Morais et al ; Ortiz de García et al ).…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the concentration of sediment, it can be observed that part of the PPCPs are enriched in the sediment during the infiltration of surface water, except IBU, into groundwater. Therefore, PPCPs in sediment have the risk of water diffusion to groundwater, and is a key indicator affecting the ecological risk to water environments [52][53][54].…”
Section: The Relationship Between Ppcp Concentration In Surface Sedim...mentioning
confidence: 99%
“…PPCPs in most areas pose a threat to the ecosystem and may have adverse effects on aquatic organisms [52]; therefore, it is worth paying attention to the control and elimination of PPCPs in sediments. It is difficult to completely remove PPCPs in sediments of urban rivers, and their accumulation in sediments will affect the survival and reproduction of benthic animals as recently reported; CAF is a psychoactive compound with high ecotoxicological relevance in many other natural water domains.…”
Section: Environmental Risks Of Ppcps In Surface Sedimentsmentioning
confidence: 99%